Strategic marketing management : eeting the global marketing challenge - Anderson, Carol H. (Houghton Mifflin, 2000)
This book is about: An introduction to strategic marketing management; Achieving competitive advantage; Implementing marketing-Mix strategies; Managing marketing efforts; ...